Strategy of Activity and Systematical Approach - Gulchehra Gulamjanovna, Gaffarova (International Journal of Psychosocial Rehabilitation, 2020)
The structural changes are going on in our republic. A structure includes connection with elements and their inter-influence on the structure. As a result, changing the structure makes the society change. The basis for the development of our Republic is the idea of forming a democratic and legal state and civil society as well. Nowadays, the path of development has been reflected in „The Strategy of Action‟. Therefore, taking into account the socio-economic changes taking place in our country and the rapid changes in the world, a strategy of action has been worked out for the future development of the Republic. In the article, the strategy of activity of development is researched.